Hubungan pola menstruasi, pola makan, asupan gizi terhadap kadar hemoglobin remaja putri - Yahmi Setyaningrum; Nurhanani Amira; Endang Sujtiati Sujtiati (Nutrition and Health Insights, 2025)
The prevalence of anemia in adolescent girls is relatively high and is a health problem that continues into the reproductive period. Anemia in adolescent girls is thought to be related to menstrual patterns, diet, and lack of nutritional intake. This study aims to analyze the relationship between menstrual patterns, diet and nutritional adequacy to hemoglobin levels in adolescent girls at Kepanjen Islamic High School. This research method uses a correlation analytic design with a cross-sectional approach. The sampling technique used is stratified sampling. The number of samples in this study was 56 female students. The instrument for collecting menstrual pattern data used a questionnaire, dietary data and nutritional adequacy used a semi-FFQ and hemoglobin level data used a portable hemoglobinometer. The results of the Spearman statistical test showed that there was a fairly strong and positive relationship between menstrual patterns (p value 0.000; r 0.815), diet (p value 0.000; r 0.629), energy, protein, fat, carbohydrate and iron adequacy and hemoglobin levels. The conclusion of this study is that the better the menstrual patterns, diet and iron adequacy in adolescent girls will reduce the risk of anemia.